Evaluation of physiological quality of sweet corn seeds under different conditions - A. A. C. Rivera; I. V. A. Fiorini; R. G. Von Pinho; H. D. Pereira; E. L. Resende; C. S. Pereira (Scientific Electronic Archives, 2019)
The objective was to evaluate the physiological quality of seeds of sweet corn in two types of packages under different storage conditions. Used supersweet corn seeds of cultivar SwB585 classified in flat sieve. The seeds were placed to soak in distilled water with GA3 at concentrations of 0, 10 and 20 mg L-1, then were placed in vacuum plastic packaging and paper packaging and stored in two environments (cold 10 °C and room temperature 25 °C). The evaluations were made by the germination test, electrical conductivity, accelerated aging and cold test. The experiment was conducted for two types of packaging, in a factorial scheme (2x3x5), corresponding to the two environments, the three doses of GA3 and the five assessment times (0, 60, 120, 180 and 240 days), with four replications. It was found thatthe packages did not influence the physiological quality of seeds, except in the cold test. However, we determined that the best preserved seed physiological potential in refrigerated at 10°C. With the passage of time of storage the gibberellic acid loses effect on seed performance. The seeds of sweet corn vigor decreases linearly with the passage of time in storage.